2021
DOI: 10.3389/fphys.2021.640898
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Trivalent Chromium Exposure Up-Regulates Lipid Metabolism in Coral Trout: The Evidence From Transcriptome Analysis

Abstract: Diet quality greatly affects an animal’s performance and metabolism. Despite the fact that trivalent chromium [Cr(III)] is considered an essential element and is widely used in nutritional supplements for animals and humans, the potential toxicity of Cr(III) is unclear. Here, liver transcriptome sequencing was performed on coral trout (Plectropomus leopardus) exposed to 200 mg kg–1 of dietary organic Cr(III) [as chromium picolinate (CrPic)] for 8 weeks. One-hundred-and thirteen differentially expressed genes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…On one hand, studies have found that a substantial increase of AKT3 expression in macrophages will reduce the expression of DHCR7 upon DNA and RNA viral infection, and the downregulation of DHCR7 in liver or liver cells promoted clearance of Zika virus and multiple viruses in vitro or in vivo . On the other hand, as DHCR7 is a vital enzyme switch between cholesterol and vitamin D production, its upregulation may reflect a switch toward increased lipid synthesis in the liver. , Besides, the upregulations of NSDHL and HMGCS1 are also related to the increase of lipid synthesis during the degradation process of liver injury. , Their depressed conditions (DHCR7, NSDHL, HMGCS1) could be reversed during self-healing or drug treatment. In our study, the downregulation of these three DEGs was related to hepatotoxicity in vivo .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, studies have found that a substantial increase of AKT3 expression in macrophages will reduce the expression of DHCR7 upon DNA and RNA viral infection, and the downregulation of DHCR7 in liver or liver cells promoted clearance of Zika virus and multiple viruses in vitro or in vivo . On the other hand, as DHCR7 is a vital enzyme switch between cholesterol and vitamin D production, its upregulation may reflect a switch toward increased lipid synthesis in the liver. , Besides, the upregulations of NSDHL and HMGCS1 are also related to the increase of lipid synthesis during the degradation process of liver injury. , Their depressed conditions (DHCR7, NSDHL, HMGCS1) could be reversed during self-healing or drug treatment. In our study, the downregulation of these three DEGs was related to hepatotoxicity in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…33,34 Besides, the upregulations of NSDHL and HMGCS1 are also related to the increase of lipid synthesis during the degradation process of liver injury. 35,36 Their depressed conditions (DHCR7, NSDHL, HMGCS1) could be reversed during self-healing or drug treatment. In our study, the downregulation of these three DEGs was related to hepatotoxicity in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Although there is no study about the function of terpenoid backbone biosynthesis in food habit domestication, it has been reported that terpenoid backbone biosynthesis plays a key role in the metabolism of animals under stressors. For example, exposure to dietary trivalent chromium up-regulated terpenoid backbone biosynthesis pathway-related genes Hmgcr , Pmvk , Mvd , Id1 , and Fdps in Coral trout ( Plectropomus leopardus ) 23 , and low temperatures activated the genes including Hmgcr , Hmgcs1 , Acat2 , Mvk , and Id1 in Grass carp ( Ctenopharyngodon idellus ) 24 . In this study, under the stimulation of different nutrients, these individuals who performed higher activity of terpenoid backbone biosynthesis could better metabolite the lipids in artificial pelleted diets.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive investigations have furnished compelling evidence demonstrating that Cr­(VI) readily permeates the cellular membrane owing to its heightened solubility, subsequently engendering the generation of reactive oxygen species (ROS) responsible for inflicting numerous oxidative injuries upon cellular organelles. , In contrast, derivatives of Cr­(III) exhibit diminished toxicity and mutagenicity relative to Cr­(VI), owing to their insolubility in water under neutral pH conditions. Moreover, Cr­(III) assumes a vital role in human metabolism, being intricately linked to the regulation of glucose, cholesterol, and triglyceride levels, maintenance of cellular membrane stability, and the synthesis as well as stability of nucleic acids and proteins. Consequently, prevailing strategies aimed at mitigating chromium pollution in the environment are primarily focused on effectuating the reduction of hexavalent chromium to its trivalent counterpart.…”
Section: Introductionmentioning
confidence: 99%